The choice of traction motors for building systems for mobile electrical systems - Кулагін, Дмитро Олександрович; Чернецький, Богдан Сергійович (Technology audit and production reserves, 2015)
The peculiarities of the choice of traction motors for different types and designs of mobile electrical systems. The analysis of the practical experience of building systems for traction drives on the basis of the selected traction motor and synthesis techniques for determination of parameters of the engine under certain requirements relative to the movement's electrical sector. The study of building systems for traction drives with different types of engines are relevant from the point of view of achieving a maximum level of energy efficiency by performing all of the listed requirements. Means of improving energy efficiency and productivity of mobile electrical systems in the complex situation on the market of energy resources to help ensure the growth of the independence of the domestic transport sector from a number of economic and political factors that have a significant impact on key indicators of work of many enterprises and the budget of private vehicle owners and ensure optimal design and more efficient work of the various sectors of the economy. As a result of the analysis has been further development of the method of determining the type and parameters of the traction motors of the rolling electrical complex by taking into account the specific requirements from the side of the actuator. In particular, the analysis of the practical experience of choosing the traction motors and synthesis methods determine the type and parameters of the traction motors with the specified requirements by rolling electrical complex, which allows for accurate selection of the type and parameters of the engine depending on operating conditions of the electrical industry.